2013
DOI: 10.1080/02701960.2013.737388
|View full text |Cite
|
Sign up to set email alerts
|

Students Delivering Health Care to a Vulnerable Appalachian Population Through Interprofessional Service-Learning

Abstract: Interprofessional student service-learning experiences are integrated into the preventive care of older adult residents of public housing in Appalachia. Receiving a Health Resources and Services Administration grant provided the College of Nursing at East Tennessee State University the opportunity to expand interprofessional clinical experiences for students by partnering with the College of Pharmacy, the College of Clinical & Rehabilitative Health Sciences, and the local public housing authority. Select facul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, McClung (2008) found leadership roles in men who stepped out of the expected norms to become nurses. M. L. Lee et al (2013) found, even as students, nurses were leaders in interprofessional collaboration in a service-learning project aiding a vulnerable population of low-income, chronically ill elderly females. Leadership is also noted in Persily's (2004) exemplar of professional practice.…”
Section: Perceptions Of Nursing By Nurses and Education Leadersmentioning
confidence: 99%
“…However, McClung (2008) found leadership roles in men who stepped out of the expected norms to become nurses. M. L. Lee et al (2013) found, even as students, nurses were leaders in interprofessional collaboration in a service-learning project aiding a vulnerable population of low-income, chronically ill elderly females. Leadership is also noted in Persily's (2004) exemplar of professional practice.…”
Section: Perceptions Of Nursing By Nurses and Education Leadersmentioning
confidence: 99%
“…Investigators have identified logistical concerns (Lee, Hayes, McConnell, & Henry, 2013), the challenges of mixed methodology (Kahlke, 2014), unpredictability in qualitative data collection (Marshall & Edgley, 2015), and the need for flexibility and ongoing self-reflection (Ortlipp, 2008) as among the pitfalls that can occur.…”
Section: Background and Significancementioning
confidence: 99%
“…9 Interprofessional service-learning student experiences have been described in the pharmacy and nursing literature. 10,11,12 Few pharmacy service-learning experiences are described as student-led. 13 Although several pharmacist-led and studentled immunizations experiences are reported, 14,15,16,17 none found have documented an interprofessional approach.…”
Section: Introductionmentioning
confidence: 99%